Digital Transformation in Public Service Management: Addressing Challenges in the Modern Era - Wahyudi, Andri (International Journal of Social Science, Education, Communication and Economics, 2024)
Digital transformation in public service management has become essential in addressing the challenges posed by contemporary society, including rising demands for transparency, efficiency, and accessibility. This article examines the impact of digital technologies on public service delivery, emphasizing the need for innovative strategies that enhance citizen engagement and improve service quality. The introduction provides a historical context for public service management and highlights the necessity for digital transformation. The literature review discusses various models and frameworks that underpin digital initiatives in the public sector. The methodology section describes the mixed-methods approach used to evaluate the effectiveness of digital transformation in public services. Results indicate that digital tools significantly enhance service efficiency, citizen satisfaction, and overall governance. The discussion highlights key findings, including the importance of leadership, infrastructure, and user-friendly interfaces in successful digital initiatives. Finally, the conclusion emphasizes the need for continuous adaptation and improvement in public service management to meet citizens' evolving needs in the digital age. This article aims to serve as a resource for policymakers, practitioners, and scholars interested in the intersection of digital technology and public administration.